Symbol the reference guide to abstract and figurative trademarks - Hyland, Angus (London, United Kingdom Laurence King Publishing, 2014)
"Symbols play an integral role in almost all branding programmes. This book explores the visual language of symbols according to their most basic element: form. Over 1,300 symbols from all over the world are included. These are organized into groups and sub-groups according to their visual characteristics, and are indexed by sector, designer and client. Case studies of classic symbols are also featured, making this an indispensable archive of identity systems for designers and researchers." -- Provided by publisher
Includes index.
Keywords: Logos (Symbols) -- Design; Logos (Symbols); Branding (Marketing)